The Entrepreneurship-Philanthropy Nexus: Nonmarket Source of American Entrepreneurial Capitalism - Zoltán J. Ács; David B. Audretsch; Ronnie J. Phillips; Sameeksha Desai (Max Planck Institute of Economics, 2007)
What differentiates American capitalism from all other forms of industrial capitalism is a historical focus on both the creation of wealth (entrepreneurship) and the reconstitution of wealth (philanthropy). Philanthropy has been part of the implicit American social contract that continuously nurtures and revitalizes economic prosperity. Much of the new wealth created historically has been given back to the community to build many of the great social institutions that have paved the way for future economic growth. This entrepreneurship-philanthropy nexus has not been fully explored by either economists or the general public. The purpose of this paper is to suggest that American philanthropists - particularly those who have made their own fortunes - create foundations that, in turn, contribute to greater and more widespread economic prosperity through knowledge creation. Analyzing philanthropy sheds light on our current understanding of how economic development has occurred, as well as the roots of American economic dominance.
Keywords: D64; M13; M14; 330; entrepreneurship; philanthropy; capitalism; knowledge; Unternehmer; Kapitalismus; Wohltätigkeit; Stiftung; Wissenstransfer; Wirtschaftswachstum; USA